Assessing the Protective Role of Cheese Consumption Against Type 2 Diabetes and Its Complications: A Mendelian Randomization Study - Shuwei Weng; Xin Guo; Chen Ding; Die Hu; Daoquan Peng (International Journal of Endocrinology, 2025)
Conclusion: This study suggests a protective role of cheese intake in reducing T2DM risk and its ophthalmic complications, potentially informing dietary recommendations for T2DM management.